ASSOCIATION OF INSULIN RESISTANCE WITH ALANINE AMINOTRANSFERASE (ALT) LEVELS AS A MARKER OF HEPATIC VISCERAL OBESITY IN OVERWEIGHT ADOLESCENTS. - DR.MAHENDRA GANDHE; DR.KALYAN GOSWAMI; DR.SWAPNALI GANDHE (International Journal of Pharma and Bio Sciences, 2013)
Insulin resistance (IR) is well known to be an established predictor of cluster of disorders such as Type 2 Diabetes mellitus(T2DM), hypertension, dyslipidemia and atherosclerosis. In non-alcoholic fatty liver disease (NAFLD), there is a documented well known fact of liver biochemical abnormality including increased alanine amino-transferase (ALT) levels. Hence, in this study we tried to ascertain whether there could be any association between insulin resistance and ALT level as a marker of visceral obesity in overweight adolescents. ALT levels were significantly higher among overweight adolescents than healthy controls. There is a close association observed in overweight adolescents with reference to the presence of cardiometabolic risk factors, IR and increased ALT levels. Markers of hepatic visceral obesity such as ALT and insulin resistance (HOMA-IR) are the important parameters for prediction of visceral obesity associated with liver in overweight adolescents.